The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3233/thc-202305
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between zirconia and titanium abutments on the stress distribution in parafunctional loading: A 3D finite element analysis

Abstract: BACKGROUND: Zirconia has become a popular biomaterial in dental implant systems because of its biocompatible and aesthetic properties. However, this material is more fragile than titanium so its use is limited. OBJECTIVES: The aim of this study was to compare the stresses on morse taper implant systems under parafunctional loading in different abutment materials using three-dimensional finite element analysis (3D FEA). METHODS: Four different variations were modelled. The models were created according to abutm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…The objective of this work was to conduct a comparative study and mechanically characterize new materials that are potential candidates for dental implantology. The obtained results agree with those of previous studies [ 19 , 22 , 23 ]. Sivrikaya et al found that zirconia abutments showed a lower stress distribution compared to that of titanium abutments, indicating that zirconia abutments may be a better choice for dental implants in patients who exhibit parafunctional habits.…”
Section: Discussionsupporting
confidence: 93%
“…The objective of this work was to conduct a comparative study and mechanically characterize new materials that are potential candidates for dental implantology. The obtained results agree with those of previous studies [ 19 , 22 , 23 ]. Sivrikaya et al found that zirconia abutments showed a lower stress distribution compared to that of titanium abutments, indicating that zirconia abutments may be a better choice for dental implants in patients who exhibit parafunctional habits.…”
Section: Discussionsupporting
confidence: 93%
“…They used the same two dental implants as in our study, but few publications have analysed the parafunctional forces over implants [29]. They focus on abutment material or occlusal splint devices [30,31]. Studies that assess the mechanical response of the bone-implant interface in bruxist patients are needed.…”
Section: Introductionmentioning
confidence: 99%